OSSIFICATION AND HYPERTROPHY OF LIGAMENTUM FLAVUM AT THORACIC SPINE - Hussain, Mubarak; Raja, Riaz Ahmed; Makhdoom, Asadullah (Journal of Ayub Medical College Abbottabad, 2014)
Background: Hypertrophy of the ligamentum flavum is a pathological condition that causes neurological symptom (radiculopathy and / or myelopathy) and usually occurs in the thoracic,2 less frequently in the cervical spine that commonly involves thoracic spine. This study was conducted to analyse the clinical presentation and outcome of surgery of ossified ligamentum flavum at thoracic spine. Methods: This case series was conducted at Department of Neurosurgery, Liaquat University of Medical and Health Sciences Jamshoro, from January 2010 to December 2012. Patients who presented with thoracic myelopathy due to ossified ligamentum flavum were included. All the patients, after detailed history, clinical examination and radiological investigation under went decompressive laminectomy at the appropriate level. Pre-operative, post-operative and neurology at 06 months follow up was recorded. The patients having thoracic myelopathy due to other causes were excluded from the study. SPSS-10 was used to analyse the data. Results: A total of 15 patients were admitted and operated (9 males, 6 females. (M:F ratio of 1.5:1). The majority of patients were in 6th decade. Backache and lower limb weakness was the presenting feature. Overall improvement in preoperative neurological status was seen in 9 (60%) patients. Neurology remained unchanged in 4 (26.6%) patients and worsened in 2 (13.3%) patients. Conclusion: The disease is common in 5th and 6th decade. Preoperative duration of symptoms significantly correlates with recovery. Keywords: Ossified, ligamentum flavum, thoracic myelopathy, laminectomy